235 Epidemiology of motor neurone disease in wales. Issue 12 (14th November 2019) - Saad, Toni; Dawson, Ken; Hirst, Claire; Baker, Idris; Lowman, Andrea; Wardle, Mark; Harding, Katharine
Abstract : Background: National registries of patients with rare disease such as motor neurone disease (MND) can lead to more reliable epidemiological estimates. Methods: The South Wales MND Network records clinical data on all patients referred to the specialist MND clinics in south Wales and diagnosed with MND. Anonymised data was accessed for analysis. The prevalence date was 23/6/2016, and all patients registered with the South Wales MND Network, alive and resident in the region on that date were included. Population estimates were obtained from Welsh Government data. Results: There were 202 people with MND on the prevalence date, of whom 122 (60.4%) were male. The median time from onset to diagnosis was 1.4 years (interquartile range 0.9–2.4 years). Prevalence in the region was 8.8 per 100, 000. This varied by local health board, with the highest prevalence seen in Aneurin Bevan University Health Board (12.1 per 100, 000), and the lowest in Abertawe Bro Morgannwg University Health Board (7.0 per 100, 000). Male:female ratio was similar for all local health boards (χ2=3.6, p=0.46). Conclusions: Our estimates of prevalence are in keeping with other European countries. Future investigation into variation in MND prevalence may provide insights into underlying mechanisms of disease.